2017
DOI: 10.1177/1352458517739975
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin: A mediator of the gut–brain axis in multiple sclerosis

Abstract: Background:The significance of the gut microbiome for the pathogenesis of multiple sclerosis (MS) has been established, although the underlying signaling mechanisms of this interaction have not been sufficiently explored.Objectives:We address this point and use serotonin (5-hydroxytryptamine (5-HT))—a microbial-modulated neurotransmitter (NT) as a showcase to demonstrate that NTs regulated by the gut microbiome are potent candidates for mediators of the gut–brain axis in demyelinating disorders.Methods, Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…The neurotransmitter serotonin is known to regulate macrophages, T cells, and dendritic cells and is partially modulated by the gut microbiome [44]. A recently suggested hypothesis propose a connection between an unbalanced microbiota and MS pathology, through SS modulation [41]. This is supported by another recent study emphasizing the potential role of tryptophan metabolism by the gut microbiota in neuroinflammation and MS [35].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The neurotransmitter serotonin is known to regulate macrophages, T cells, and dendritic cells and is partially modulated by the gut microbiome [44]. A recently suggested hypothesis propose a connection between an unbalanced microbiota and MS pathology, through SS modulation [41]. This is supported by another recent study emphasizing the potential role of tryptophan metabolism by the gut microbiota in neuroinflammation and MS [35].…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between MS and the serotonergic system (SS), of which serotonin’s main metabolite 5-HIAA is a part, is currently not well understood. Previous studies have shown alterations in the SS in MS patients and underlined the necessity of a deeper characterization of the role of SS in MS pathology [40,41]. Fluoxetine, a candidate drug for repurposing that increases serotonin levels in the CNS, is now clinically tested as a neuroprotective treatment for SPMS patients [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…5-HT is released from enterochromaffin cells of the gastric mucosa in response to various stimuli including signals from gut microbiota (15)(16)(17). Although 5-HT is a well-known neurotransmitter that is associated with emotion and behaviour, about 90% of 5-HT in the body is produced in the digestive tract where it is involved in the detection of resource availability and regulation of bowel movement.…”
Section: Effect Of Probiotic On Gut-brain Axismentioning
confidence: 99%
“…Gut microbiota stimulates host intestinal cells to produce 5-HT. An imbalance of 5-HT in the brain can lead to depression, whereas peripheral dysregulation of this neurotransmitter has been linked to a variety of diseases (1,2,7,12,15,16,(18)(19)(20)(21). In this study we found that treatment with L. plantarum IS-10506 caused an increase in brain 5-HT level in rats relative to the control group.…”
Section: Effect Of Probiotic On Gut-brain Axismentioning
confidence: 99%
“…As trocyte 45 Microbe-associated molecular patterns 46 Major his tocompatibility complex Π 47 Aryl hydrocarbon receptor 48 Indole-3-aldehyde 49 Indole-3-propionic acid 50 T helper 17 51 Interleukin 17A…”
mentioning
confidence: 99%